Using GIS to study the analysis of flooding areas south of Himreen dam to the north of Baquba district/ Iraq - Mohammed, Ammar Hussein (Journal of natural sciences, life and applied sciences, 2019)
This study describes the analysis of flooding areas south of Himreen dam to the north of Baqubah district. The study aims at different measurements of flooding in a simulated manner. to minimize the amount of damage that these areas could suffer in actual flooding. Stream measurements and flow forecasting are the basis for understanding flood mechanics. And select it at each river station for a certain time period. . This research used different study methods. The HEC-RAS model was used with ArcGIS for flood design and analysis. Based on the available data, the areas south of Himreen Dam to the north of Baqubah district were selected as a study area. The area of the Hamrin reservoir is about 347 km², with a storage capacity of 2. 06 billion cubic meters under normal conditions. It provides water for some 300, 000 hectares of lands. The maximum area of the reservoir is about 450 km², and the maximum storage capacity of 3. 95 billion cubic meters In flood conditions. The information in HEC-RAS is to re-create the input and output files. In addition to the time format in the geographic database data model. A statement of capabilities according to the movement drawn.